Effect of Anular Closure on Disk Height Maintenance and Reoperated Recurrent Herniation Following Lumbar Diskectomy: Two-Year Data - Ledic, Darko; Vukas, Duje; Grahovac, Gordan; Barth, Martin; Bouma, Gerrit J.; Vilendecic, Milorad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Objective To assess the potential benefits of disk reherniation reduction and disk height maintenance in limited diskectomy combined with the implantation of the anular closure device.Summary and Background Data Postoperative disk height loss is apparent in most patients undergoing lumbar diskectomy for herniated nucleus pulposus. Less favorable patient outcomes are associated with significant loss in disk height that can occur after aggressive disk tissue removal. More conservative disk removals, however, are often burdened by the increased risk of recurrent disk herniation.Methods Two prospective single-arm studies on patients treated with limited diskectomy and an anular closure device were conducted. Outcome measures included disk height maintenance relative to preoperative values, Oswestry Disability Index, back pain, leg pain, and complications such as reherniations. Patients were evaluated preoperatively and postoperatively at 6 weeks and at 3-, 6-, 12-, and 24-month time points.Results A total of 75 patients were included in this cohort consisting of 40 men and 35 women with an average age of 40 years. Disk height maintenance within the group overall was 90% at 24 months. Overall, 97% of the treated disks demonstrated disk height maintenance of at least 75% of preoperative levels at 12 months and 92% at 24 months. Disk height maintenance was correlated with less nucleus removal. Patient disability, back pain, and leg pain were significantly improved from preoperative levels at 6 weeks and maintained over the course of study. There was a single symptomatic reherniation requiring surgical intervention within this series.Conclusions Limited lumbar diskectomy combined with the use of an anular closure device provided very low rates of disk reherniation and exhibited excellent disk height maintenance and sustained disability, leg pain, and back pain improvement within a 24-month postoperative study period. As with prior diskectomy studies, disk height maintenance was correlated with lower nucleus removal, although recurrence was less than in prior reports of limited diskectomy. Anular closure may allow for achievement of both objectives.
Keywords: anular closure; diskectomy; disk height; reherniation